Charge Tunneling along Short Oligoglycine Chains. Issue 49 (9th October 2015) - Baghbanzadeh, Mostafa; Bowers, Carleen M.; Rappoport, Dmitrij; Żaba, Tomasz; Gonidec, Mathieu; Al‐Sayah, Mohammad H.; Cyganik, Piotr; Aspuru‐Guzik, Alan; Whitesides, George M.
Abstract: This work examines charge transport (CT) through self‐assembled monolayers (SAMs) of oligoglycines having an N‐terminal cysteine group that anchors the molecule to a gold substrate, and demonstrate that CT is rapid (relative to SAMs of n ‐alkanethiolates). Comparisons of rates of charge transport‐using junctions with the structure Au TS /SAM//Ga2 O3 /EGaIn (across these SAMs of oligoglycines, and across SAMs of a number of structurally and electronically related molecules) established that rates of charge tunneling along SAMs of oligoglycines are comparable to that along SAMs of oligophenyl groups (of comparable length). The mechanism of tunneling in oligoglycines is compatible with superexchange, and involves interactions among high‐energy occupied orbitals in multiple, consecutive amide bonds, which may by separated by one to three methylene groups. This mechanistic conclusion is supported by density functional theory (DFT). Abstract : Superexchange Tunneling : Self‐assembled monolayers (SAMs) of oligoglycines ((Gly) n, n =0–5) are more conductive by tunneling than are SAMs of alkanethiolates. This difference is quantified experimentally and theoretically. Density functional calculations identify the details of the orbitals and electronic couplings involved in superexchange tunneling.